Determining noble gas partitioning within a CO2–H2O system at elevated temperatures and pressures. (15th June 2015) - Warr, Oliver; Rochelle, Christopher A.; Masters, Andrew; Ballentine, Christopher J.
Abstract: Quantifying the distribution of noble gases between phases is essential for using these inert trace gases to track the processes controlling multi-phase subsurface systems. Here we present experimental data that defines noble gas partitioning for two phase CO2 –water systems. These are at the pressure and temperature range relevant for engineered systems used for anthropogenic carbon capture and geological storage (CCS) technologies, and CO2 -rich natural gas reservoirs (CO2 density range 169–656 kg/m 3 at 323–377 K and 89–134 bar). The new partitioning data are compared to predictions of noble gas partitioning determined in low-pressure, pure noble gas–water systems for all noble gases except neon and radon. At low CO2 density there was no difference between measured noble gas partitioning and that predicted in pure noble gas–water systems. At high CO2 density, however, partition coefficients express significant deviation from pure noble gas–water systems. At 656 kg/m 3, these deviations are −35%, 74%, 113% and 319% for helium, argon, krypton and xenon, respectively. A second order polynomial fit to the data for each noble gas describes the deviation from the pure noble gas–water system as a function of CO2 density. We argue that the difference between pure noble gas–water systems and the high density CO2 –water system is due to an enhanced degree of molecular interactions occurring within the dense CO2 phase due to the combined effect of inductive and dispersive forces acting on the noble gases. As the magnitude of these forces are related to the size and polarisability of each noble gas, xenon followed by krypton and argon become significantly more soluble within dense CO2 . In the case of helium repulsive forces dominate and so it becomes less soluble as a function of CO2 density.